Haeresis 101 in the Liber de haeresibus of St. John of Damascus, and the Quranic Arguments against the Icons (Forum Theologicum Sardicense, 2025)
The author analyses the Qur‘anic doctrinal arguments presented in Muslim works on icon worship in the Christian Church and examines their possible influence on the writings of St. John Damascene..
Keywords: History of Religion; Christianity and Islam; Religious Studies